Antennal Sensilla in the Parasitoid Sclerodermus sp. (Hymenoptera: Bethylidae). Issue 1 (5th April 2015) - Zhou, Chang-Xiang; Sun, Xiao; Mi, Feng; Chen, Jingyuan; Wang, Man-Qun
Abstract : Parasitoid wasps of the genus Sclerodermus (Hymenoptera: Bethylidae) are an important natural enemy of the Japanese pine sawyer beetle Monochamus alternatus Hope (Coleoptera: Cerambycidae). In this study, we used scanning electron microscopy to examine the external morphology of the antennal sensilla of Sclerodermus sp. Antennae of females and males comprised the scape, pedicel, and 11 flagellomere segments. Based on the morphology of the sensilla in each sex, seven types of sensillum were identified: sensilla trichodea (Tr.1, Tr.2 and Tr.3), sensilla basiconica (Ba.1, Ba.2, and Ba.3), sensilla styloconica (St.1 and St.2), sensilla placodea, sensilla coeloconica, sensilla squamiforma, and Bohm's bristles. Tr.2, Ba.1, and St.1 were only found in females, whereas Ba.2, Ba.3, and St.2 were only observed in males. Sensilla placodea were the most common, given that they occur on the antennae of many parasitoid Hymenoptera, whereas sensilla Tr were the most abundant, being distributed over the entire antennal surface. These sensilla are likely to have roles in the host locating and habitat searching behavior of adult Sclerodermus wasps. Therefore, our findings provide a basis for further studies of the host location behavior of this and other species of parasitic wasp.